Il ritorno dei personaggi e le trasformazioni della borghesia in Galdós - Scotto di Carlo, Assunta Claudia (Status Quaestionis, 2017)
The representation of the middle class and of its transformations is the mainstay of Benito Pérez Galdós’s vast literary production. Being a great connoisseur of Balzac, the writer was able to grasp the importance that some narrative techniques had in the development of the modern realist novel in Spain. The contribution focuses on the return of the characters, whose use is linked to the will to represent the bourgeois society at a precise historical moment. Galdós creates the illusion of a continuous narrative, in which there are no boundaries between the novels and the specific events they narrate: the characters reappear in the different texts and carry with them their stories that are, hence, enriched and modified. Subsequently, through some examples, attention will be paid to the connection between the recursiveness of the characters and the change of the writer's view on the bourgeoisie that has betrayed its own ideals.